Strategi Penerapan Kurikulum Merdeka untuk Meningkatkan Kreativitas dan Kemandirian Belajar Siswa - Hidayah, Wahyu Nurul; Mustahyatun (CV. Global Cendekia Inti, 2025)
The implementation of the Merdeka Curriculum in Indonesia emerges as an effort to improve the quality of education by emphasizing student-centered learning. This curriculum aims to foster students’ creativity and learning independence through project-based learning, differentiated instruction, and teacher flexibility in designing strategies that meet students’ needs and characteristics. This study aims to analyze strategies for implementing the Merdeka Curriculum to enhance students’ creativity and independent learning in schools. The research method employed is a literature study by analyzing various academic sources, regulations, and research findings related to the implementation of the Merdeka Curriculum. The results indicate that effective strategies include project-based learning, the integration of digital technology into classroom activities, teacher-student collaboration in designing learning processes, and providing reflection opportunities for students to evaluate their learning experiences. These findings highlight that the success of implementing the Merdeka Curriculum is strongly influenced by teacher readiness, school environment support, and students’ active involvement in the learning process. Therefore, a well-planned and adaptive implementation strategy can significantly enhance students’ creativity, independence, and 21st-century skills needed to face global challenges.